THE EFFECT OF PRE-MEDICATION WITH ORAL STEROIDS ON INTRA-OPERATIVE BLEEDING IN PATIENTS WITH CHRONIC RHINOSINUSITIS UNDERGOING FUNCTIONAL ENDOSCOPIC SINUS SURGERY - Saira Iftikhar; Ayesha Jawad; Mumtaz Ahmad Umar; Farhan Ahmed; Maimoona Shafqat; Seema Naveed (Journal of Ayub Medical College Abbottabad, 2024)
Background: An inflammation of the nasal and paranasal sinus mucosa that lasts longer than three months is known as chronic rhinosinusitis. When corticosteroids and other medicinal treatments fail to relieve a patient’s symptoms, then functional endoscopic sinus surgery (FESS) is a commonly performed procedure to alleviate the symptoms. The aim of the study was to evaluate the impact of oral steroids given prior to surgery on intraoperative bleeding in patients having functional endoscopic sinus surgery for chronic rhinosinusitis. Methods: The study was conducted in ENT Department of Shifa Foundation Community Health Centre (SFCHC) and Shifa International Hospital (SIH) Islamabad, in a period of three years from June 2019 to June 2021. A total of 72 patients consisting of 36 patients in study group and 36 in control group, fulfilling the inclusion criteria were included in the study. Per-operative bleeding was assessed by measuring the amount of blood collected in suction bottle at the end of the procedure (the amount of saline used during the procedure was subtracted) and the number of surgical gauzes stained with blood (1 partially stained gauze = 5 ml and 1 completely stained gauze = 10 ml). The surgeon performing the surgery was unaware of the study group of the patient. All the collected data was entered and analyzed with SPSS v. 25. Results: The mean age of group A (35.39±13.86 vs. 29.83±15.86, p-value > 0.05) was similar to group B. There was male dominance in both group (69.4% vs. 72%) males in group A and group B. Nasal obstruction and nasal discharge was observed in all patients of both groups. Post nasal drip (88.9% vs. 88.9%), headache (97.2% vs. 91.7%) and facial pain (97.2% vs. 94.4%) was present in majority patients of both groups without any significant (p-value >0.05) difference. Both the groups were compared on the basis of amount of blood loss per-operatively and it was seen that the mean blood loss in group A was (164.03±42.99 ml) significantly (p-value <0.05) lower as compared to (215.83±39.397 ml) in group B. Conclusion: This study showed that individuals with nasal polyps receiving preoperative steroids could successfully lower their perioperative morbidity, specifically intraoperative haemorrhage, after undergoing functional endoscopic sinus surgery.